Hubungan Jumlah Trombosit Dan D-Dimer Pasien Covid-19 Di RSI Fatimah Banyuwangi - Rosidah Rosidah; Riski Maulana; Anik Eko Novitasari; Lina Madyastuti (Jurnal Medika Nusantara, 2024)
According to the Indonesian Ministry of Health (2020), Corona virus (CoV) is a large family of viruses that can cause illness ranging from mild, moderate to severe symptoms. Corona virus is zoonotic (transmitted between animals and humans). Research says that SARS-CoV is transmitted from civet cats (civetcats) to humans and MERS-CoV from camels to humans. Platelets are an important component in the hemostatic response which are closely related to other hemostatic components (NugrahaGilang, 2017). Platelets were obtained from the cytoplasm of megakaryocytes (80-150 m in size). D-dimer is a fibrin degradation product formed during the degradation of blood clots by fibrinolysis. Elevated D-dimer in the blood is a marker of suspected thrombosis. Platelet examination using the Direct method. Analysis of platelet levels with an average of 379.231.6 cells/permicroliter of blood. The purpose of this study was to determine the relationship between platelet levels and D-dimer in Covid-19 patients. The conclusion of this study is that there is a relationship between the results of the examination of platelet levels with D-dimer levels, if the platelet levels increase, the D-dimer levels increase.